21st Century Learning Innovations and Their Application in Marketing Management Courses - Jamilah Jamilah (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
This study aims to explore the implementation of 21st-century learning innovations and their application in Marketing Management courses in higher education. Rapid developments in technology and industry demand learning approaches that not only emphasize theoretical understanding but also foster essential skills such as critical thinking, problem-solving, collaboration, communication, and digital literacy. This research employed a qualitative descriptive approach with a case study design. Data were collected through classroom observations, in-depth interviews with lecturers and students, student perception questionnaires, and document analysis of course syllabi, learning materials, learning management systems, and project assignments. The findings reveal that the integration of innovative learning methods, including Project-Based Learning, Case-Based Learning, digital marketing simulation tools, and collaborative learning activities, significantly enhanced student engagement and learning experiences. The application of these innovations enabled students to connect marketing theories with real-world practices, improve higher-order thinking skills, and develop creativity in marketing strategies. Despite these positive outcomes, several challenges were identified, such as lecturers’ readiness, students’ adaptation to active learning approaches, technological limitations, and time management issues. Overall, the study concludes that 21st-century learning innovations are highly relevant to Marketing Management courses and play a crucial role in preparing students for the demands of the contemporary marketing industry.